2017
DOI: 10.1177/0363546517709777
|View full text |Cite
|
Sign up to set email alerts
|

Midterm and Long-term Results of Medial Versus Lateral Meniscal Allograft Transplantation: A Meta-analysis

Abstract: Meta-analysis indicated that 85.8% of medial and 89.2% of lateral meniscal allograft transplants survive at midterm (5-10 years) while 52.6% of medial and 56.6% of lateral meniscal allograft transplants survive long term (>10 years). Patients undergoing lateral meniscal allograft transplantation demonstrated greater pain relief and functional improvement than patients undergoing medial meniscal allograft transplantations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 22 publications
(31 reference statements)
7
43
0
2
Order By: Relevance
“…Our subgroup analysis showed that lateral MAT produced better outcomes compared with medial MAT in two out of the four PROMs, although failure rates were comparable; this is in agreement with Bin et al 15 who published a meta-analysis of long-term outcomes of medial vs. lateral MAT and with other authors of cohort studies. 35,45,49 It is unclear why medial MAT is associated with significantly worse reported outcomes and graft survivorship.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our subgroup analysis showed that lateral MAT produced better outcomes compared with medial MAT in two out of the four PROMs, although failure rates were comparable; this is in agreement with Bin et al 15 who published a meta-analysis of long-term outcomes of medial vs. lateral MAT and with other authors of cohort studies. 35,45,49 It is unclear why medial MAT is associated with significantly worse reported outcomes and graft survivorship.…”
Section: Discussionsupporting
confidence: 92%
“…We also identified areas in which there is need for more and better quality evidence, specifically concerning the role of preoperative chondral damage, sport level, time from meniscectomy, and smoking status, whose impact on clinical outcome is still controversial. Several systematic reviews and meta-analyses have been published in the last decade about MAT; these, however, were mostly introductory in their nature, [7][8][9][10][11][12] focused primarily on outcomes in general, 2,3,13,14 or evaluated one single predictor in detail, such as laterality, 15 the impact of concomitant procedures, 16 or the type of graft fixation. 17 Other reviewers considered particular aspects, such as the chondroprotective role of MAT 5 or the feasibility of sports activity after recovery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,14 However, these studies are heterogeneous in terms of indications and techniques because they included patients with either medial or lateral compartment pathology due to valgus or varus malalignment. Because it is known that medial and lateral MATs show significantly different outcomes, with lateral MATs outperforming medial MATs in terms of functional improvement and pain relief, 15 it is necessary to delineate the outcomes between these procedures.…”
Section: See Commentary On Page 261mentioning
confidence: 99%